Penerapan Model Pembelajaran Contextual Teaching And Learning Dalam Meningkatkan Hasil Belajar Materi Kegiatan Ekonomi Pada Siswa Kelas V SD - Romi Y. Mongdong (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to improve the learning outcomes of social studies through the model of learning This study aims to improve the learning outcomes of economic activity material through the application of CTL learning model in grade V students of SD Inpres Perumnas Uluindano Tomohon. The research method used in this study is classroom action research (PTK) according to Kemmis and Mc. Taggart, (Aqib zainal 2006; 31) consists of 4 stages, namely: This research was conducted in class V of SD Inpres Perumnas Uluidano Tomohon with the calculation of the presentation of the completeness of student learning outcomes in cycle 1 which reached 66.3% so that in cycle 1 it was not successful and continued in cycle 2 in the second cycle which was carried out increased to 91.1%. The conclusion of this study is how the application of the CTL learning model can improve the learning outcomes of fifth grade students of SD Inpres Perumnas Uluindano Tomohon